2019
DOI: 10.1177/1362361319851422
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of the National Autistic Society EarlyBird parent support programme

Abstract: The EarlyBird programme is a group-based psychoeducation intervention for parents of young children with autism. Although it is widely used in the United Kingdom, the evidence base for the programme is very limited. Using a mixed method, non-randomised research design, we aimed to test (1) the acceptability of the research procedures (recruitment, retention, suitability of measures), (2) the parental acceptability of EarlyBird (attendance, views of the programme, perceived changes) and (3) the facilitator acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The results from parents on both the EB/EBP and Autism Cares programmes showed strong acceptability support for these programmes. These results are largely in line with previous research on both EB/EBP and PET (Cutress & Muncer, 2014; Engwall & MacPherson, 2003; Palmer et al, 2020; Schultz et al, 2011). Parents suggested a range of potential adaptations reflective of the needs of multi-cultural settings, such as interpreters in sessions, creating videos with local parents and children and mixed thoughts about the need to translate materials into primary languages other than English.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results from parents on both the EB/EBP and Autism Cares programmes showed strong acceptability support for these programmes. These results are largely in line with previous research on both EB/EBP and PET (Cutress & Muncer, 2014; Engwall & MacPherson, 2003; Palmer et al, 2020; Schultz et al, 2011). Parents suggested a range of potential adaptations reflective of the needs of multi-cultural settings, such as interpreters in sessions, creating videos with local parents and children and mixed thoughts about the need to translate materials into primary languages other than English.…”
Section: Discussionsupporting
confidence: 91%
“…To date, more than 27,000 families in 14 countries have attended the 12-week group-based programmes. The majority of research on EB/EBP reported positive outcomes, although the evidence base comprised mostly lower-level strength and was exclusively from high-income countries (HICs) (Dawson-Squibb et al, 2019; Palmer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some other programs specifically address these issues (Ingersoll & Wainer, 2011; Kirkpatrick et al, 2019; Sharp et al, 2014). Palmer et al (2019) have recently used semi-structured interviews to explore facilitators’ and parents’ point of view on a group-based psychoeducational program for parents of children with autism. They tested the acceptability of a program and its associated research procedures, for parents and facilitators, with the aim to assess feasibility of a more pragmatic, controlled trial of autism-related parent support programs.…”
Section: Discussionmentioning
confidence: 99%
“…One of the psychoeducational groupbased programs, primarily developed to support parents of young children with ASD, described in the literature is the EarlyBird designed by the National Autistic Society (NAC) in the UK (Shields, 2001). This three-month program provides post-diagnostic support for families of children younger than 5 years (Palmer et al, 2020) and aims at improving child social communication skills and reducing problem behaviour by educating parents about autism and building their competence and confidence to meet the needs of their children (Shields, 2001). The program was designed to include six families who participate at eight weekly group sessions each lasting three hours and three home visits by practitioners who observe parent-child interactions.…”
Section: Psychoeducation-based Intervention Programs For Families With Asdmentioning
confidence: 99%
“…The program was designed to include six families who participate at eight weekly group sessions each lasting three hours and three home visits by practitioners who observe parent-child interactions. During group sessions, the video clips from home visits are used to provide feedback; also, parents are encouraged to share experiences and support each other (Palmer et al, 2020;Shields, 2001). The feasibility studies conducted in various cultural contexts of this program have demonstrated parents' high levels of satisfaction with the courses, their usefulness as well as positive outcomes in parents' learning how to manage children's behaviour or their own stress (Dawson-Squibb & de Vries, 2020;Dawson-Squibb et al, 2019;Palmer et al, 2020).…”
Section: Psychoeducation-based Intervention Programs For Families With Asdmentioning
confidence: 99%